Coordination strategies between UAV and AUVs for ocean exploration - P. B. Sujit (2009)
Autonomous underwater vehicles (AUVs) have limited and low bandwidth communication capabilities. In order to communicate a host, they need to surface. To increase the operational period of the AUVs and decrease the surfacing time, we deploy a single Unmanned aerial vehicle (UAV) that cooperates with AUVs in performing an ocean exploration mission efficiently. A team of AUVs are deployed in the ocean and surface when their mission leg is completed. The UAV flies over the AUVs, acquires the information, and provides a new mission plan to the AUVs. The UAV has to meet all the AUVs and reach the base station within a prescribed sortie time. However, the AUVs may not complete the assigned task and may surface anywhere along the mission plan. Hence, the UAV has to take the uncertainty of AUV surfacing into account while generating the next mission plan to the AUV. We develop a robust route planning algorithm for the UAV and path generation algorithm for the AUV such that the UAV always reaches the base station within the sortie time limit. Theoretical results are presented to show the robustness of the algorithms. Simulations are carried out to show how the mission is accomplished.